Fulfilling basic needs in Baja California: Myths and reality - Guadalupe Ortega Villa (Estudios Fronterizos, 2000)
This paper seeks to review the studies that assess the satisfaction of basic needs in our country. A particular emphasis is placed on Baja Californias´s position within the national setting. Furthermore, the results are contrasted with a study that addresses exclusively the case of Baja California, and afterwards clarify the results reported on the studies of national coverage with regards to this state. Finally, some remarks are presented that pertain to the position of such state in the country as a whole and also to the indicators that were used.